2020
DOI: 10.3390/ma13020302
|View full text |Cite
|
Sign up to set email alerts
|

Reinforced Spun Concrete Poles—Case Study of Using Chemical Admixtures

Abstract: The current research paper is focused on the experimental investigation of features of chemical admixtures (superplasticizers C-3, ‘Dofen’ and formaldehyde resin ACF-3M) utilizing in reinforced spun concrete structures. For the sake of comparison, the results of studying the effects of chemical admixtures on physical and mechanical properties on vibrated and spun concrete are provided. As a separate part of spun concrete products, the supporting poles of overhead power lines are introduced. The results obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 16 publications
(25 reference statements)
1
13
0
Order By: Relevance
“…Speaking about spun concrete products (including the supporting poles of overhead power lines), it should be mentioned that their production technology is specific, which results in the different concrete structure and texture and a smaller value of the residual water-cement ratio (W/C) residual than those in regular vibrated concrete [ 24 ]. The performed tests have shown the high resistance and reliability of spun concrete structures [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Speaking about spun concrete products (including the supporting poles of overhead power lines), it should be mentioned that their production technology is specific, which results in the different concrete structure and texture and a smaller value of the residual water-cement ratio (W/C) residual than those in regular vibrated concrete [ 24 ]. The performed tests have shown the high resistance and reliability of spun concrete structures [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the effective measures to improve the durability of concrete is using water-soluble chemical admixtures [ 26 , 27 , 28 ]. As shown by the research, chemical admixtures can decrease the initial water-cement ratio, not decreasing such concrete properties as workability and slump [ 24 ]. Positive qualitative mechanical characteristics of spun concrete with these admixtures are well known, but the behavior of these structures under long-term exposure to the salt environment and temperature changes have not been sufficiently investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kliukas, Jaras, and Lukoševičienė in [6] found that each phase of the concrete centrifugation process has a specific rotational speed, which depends on the dimensions of the element and the time needed to obtain the selected speed. According to [6], the duration of the first phase should be 3-4 min, the second and third phase should be 1-2 min, and the fourth phase should be 10-15 min.…”
Section: Introductionmentioning
confidence: 99%
“…Kliukas, Jaras, and Lukoševičienė in [6] found that each phase of the concrete centrifugation process has a specific rotational speed, which depends on the dimensions of the element and the time needed to obtain the selected speed. According to [6], the duration of the first phase should be 3-4 min, the second and third phase should be 1-2 min, and the fourth phase should be 10-15 min. It should be noted that the centrifugation time of an element in a steel form also depends on the initial water-cement ratio of the concrete mix and the pressure caused by centrifugal force, depending on the rotational speed and the diameter of the product.…”
Section: Introductionmentioning
confidence: 99%